The Insha’i Structure in The Openings of Omar Abu Risha’s Poems: A Descriptive-Analytical Study/ البنية الإنشائية في استهلالات قصائد عمر أبي ريشة: دراسة وصفية تحليلية - Ruqaya Saadoun Rahim; Latef Mahmoud Muhammad (Ijaz Arabi Journal of Arabic Learning, 2026)
This research examines Inshā’ī sentences in the openings of Omar Abu Risha’s poems, focusing on their role in directing the meaning of the text and highlighting its emotional and expressive nature. The study reveals that these sentences constitute a central element in shaping the poetic opening, granting it the ability to attract attention and effectively convey emotions and ideas. The research classifies the Inshā’ī sentences in the openings, traces their patterns and frequencies, and links each type to its textual function.